2011
DOI: 10.1590/s2179-83972011000200017
|View full text |Cite
|
Sign up to set email alerts
|

Consenso de especialistas sobre o implante por cateter de biopróteses valvares para o tratamento da estenose aórtica de alto risco cirúrgico: relato da Sociedade Brasileira de Hemodinâmica e Cardiologia Intervencionista

Abstract: Surgical replacement of the aortic valve is the therapy of choice for patients with severe symptomatic aortic stenosis. However, surgical risk increases significantly with age and with the association of comorbidities. In this clinical context, transcatheter aortic-valve implantation must be considered as a valid and effective therapeutic alternative. The purpose of this Consensus is to provide a critical review of all the evidence and recent advances related to transcatheter aorticvalve implantation and summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…published data have demonstrated the decrease of vascular conditions with a combination of newer generations of devices with a smaller diameter, integrated with a better screening of patients and increased performer's experience. (12,16,17) Vascular complications followed-up from 30 days to one year after TAVI showed that the main complications were venous dissection (62.8%), vascular perforation (31.3%), local hematoma (22.9%), retroperitoneal bleeding (9.5%), pseudoaneurysm (3.4%), and gastrointestinal ischemia (1.6%). The most time-consuming procedures and those that used more contrast had major complications, besides increasing patients' length of stay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…published data have demonstrated the decrease of vascular conditions with a combination of newer generations of devices with a smaller diameter, integrated with a better screening of patients and increased performer's experience. (12,16,17) Vascular complications followed-up from 30 days to one year after TAVI showed that the main complications were venous dissection (62.8%), vascular perforation (31.3%), local hematoma (22.9%), retroperitoneal bleeding (9.5%), pseudoaneurysm (3.4%), and gastrointestinal ischemia (1.6%). The most time-consuming procedures and those that used more contrast had major complications, besides increasing patients' length of stay.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to death from 30 days to one year, patients with vascular disorders had a higher mortality rate (p = <0.0001). (16) The confusional state present in a large number of patients was solved after they were referred to the ward. No persistent case was reported.…”
Section: Resultsmentioning
confidence: 99%
“…28 This association, however, has not been well established for TAVI. 29 The previously published consensuses controversially indicate that the number of procedures required for certification and maintenance of competence in TAVI ranges from 10 cases (no established interval between cases) 13 to 2 cases/month or 20 cases/year.…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that the multidisciplinary team involved in patient selection and performance of procedures should receive specific theoretical and practical training to acquire competence. 13,14 Supplementary teaching methods, which include the use of simulators, practice using animal models, courses, and symposia are recommended, while the supervision of more experienced surgeons (proctors) is essential at the beginning of the learning curve. In turn, the number of patients to be treated at this stage in order to attain the desired clinical outcomes is yet to be established.…”
mentioning
confidence: 99%
“…Os critérios gerais para seleção de pacientes para o implante transcateter de prótese valvar aórtica são: presença de EAo severa e sintomática, idade acima de 80 anos ou alta probabilidade de mortalidade e morbimortalidade cirúrgica, presença de comorbidades que elevem o risco da cirurgia cardíaca tradicional e acesso vascular com condições morfológicas e anatômicas para o procedimento por cateter, visto que as abordagens podem ser percutânea ou transventricular (transapical) 3 .…”
Section: Introductionunclassified